Hypothetical Learning Trajectory Based on Ethnomathematics - Sinaga, Ferry Indra Sakti (LPPM Institut Pendidikan Nusantara Global, 2024)
Ethnomathematics is the study of the relationship between mathematics and culture. The culture in question is related to the habits of human behavior in their environment. It is intended that through ethnomathematics, students can better understand mathematical concepts and their culture so as to create meaningful learning. It is important for teachers to develop a mathematics learning model that is meaningful to students from the aspects of content and process. One of the efforts that can be made is to design an ethnomathematics-based Hypothetical Learning Trajectory (HLT) in mathematics learning. The method used in writing this article is literature review. Based on supporting theories, it can be concluded that HLT is a learning design that includes student learning activities based on initial understanding abilities and student characteristics to achieve higher understanding abilities. HLT consists of three components, namely learning objectives, learning activities and learning process hypothesis. HLT in material form is in the form of context and content related to culture-based environment. Developing ethnomathematics-based HLT means using cultural values contextually by considering learning obstacles, material linkages, learning stages that are in accordance with students' thinking abilities, methods used by students and the carrying capacity of learning.